Comparative characteristics of methods of assessing the level of social and economic development of a regional social and economic system - A. V. Alexeev; I. V. Kuznetsova (Новые технологии, 2018)
The article compares main methods of assessing the level of social and economic development of a regional system. The subject of the study are approaches to assessing the level of social and economic development of the region. The authors conclude that it is necessary to combine several techniques and methods for assessing socio-economic development with a view to obtaining a synergistic effect from their use.